Diffusion‐weighted imaging using readout‐segmented echo‐planar imaging, parallel imaging, and two‐dimensional navigator‐based reacquisition in detecting acute optic neuritis. Issue 3 (6th August 2015) - Wan, Hailin; Sha, Yan; Zhang, Fang; Hong, Rujian; Tian, Guohong; Fan, Heng
Abstract : Purpose: To evaluate the accuracy of diffusion‐weighted imaging (DWI) in comparison to contrast‐enhanced, fat‐suppressed T 1 ‐weighted imaging (CET1WI) in detecting acute optic neuritis (ON). Materials and Methods: The clinical data and magnetic resonance imaging (MRI) findings of 42 patients who presented with decreased vision were retrospectively reviewed. Both 3.0T MRI DWI and CET1WI orbital imaging studies were performed. Two neuroradiologists independently evaluated the DWI and CET1WI. The sensitivity, specificity, and accuracy of the DWI and CET1WI were individually calculated using the clinical diagnosis as the reference standard. The interobserver and intraobserver reliability of DWI and CET1WI were assessed by using a weighted Cohen's kappa (κ) test; a value of P  < 0.05 was set as the threshold for statistical significance. Results: Of the 42 patients, 34 patients (41 nerves) had clinically confirmed acute ON, two had ischemic optic neuropathy, and three had chronic recurrent ON. The sensitivities of DWI and CET1WI for acute ON were 82.9–82.9% and 68.3–85.4%, respectively; the specificities were 81.4–83.7% and 79.1–93.0%, respectively; and the accuracies were 82.1–83.3% and 82.1–90.0%, respectively. The interobserver kappa values were 0.596–0.643 and 0.694–0.734 for DWI and CET1WI, respectively; the intraobserver kappa values were 0.809–0.905 and 0.834–0.924 for DWI and CET1WI, respectively (each P  < 0.0001). Conclusion: Given that its sensitivity and specificity are similar to those of dedicated CET1WI for acute ON, DWI can play an important complementary role in detecting acute ON, especially in atypical ON cases, and can provide a quantitative modality that can be used to evaluate axonal damage in the optic nerves. J. MAGN. RESON. IMAGING 2016;43:655–660.